2004
DOI: 10.2320/matertrans.45.2219
|View full text |Cite
|
Sign up to set email alerts
|

The Orientation Distribution of Ferrite Grains Dynamically and Statically Transformed from Heavily Deformed Austenite

Abstract: The orientation distribution of ferrite grains formed by dynamic and static transformation was examined using the electron backscattered diffraction technique. The orientation of ferrite grains, transformed both dynamically and statically from deformed austenite, showed a large deviation from the Kurdjumov-Sachs (K-S) orientation relationship. The deformed austenite grain structure modeled using Ni-30Fe alloy showed inhomogeneous and localized deformations within the austenite grains. A large orientation varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…There is a good possibility that the orientation of the mother austenite near the grain boundary may deviate from that of the representative orientation of the grain, due to the pre-deformation. 32,33) Deformation after ferrite nucleation was also reported to effectively aggravate the ferrite orientation relationship with the mother austenite. 34) Figure 7 shows the results of the application of a small load (3 kNϭ26.5 MPa) during the ferrite transformation in a 0.15C-1.4Mn-0.3Si-0.02Ti-0.006B-0.03Al steel.…”
Section: Effect Of Applied Stress On the Ferrite Grain Formationmentioning
confidence: 99%
“…There is a good possibility that the orientation of the mother austenite near the grain boundary may deviate from that of the representative orientation of the grain, due to the pre-deformation. 32,33) Deformation after ferrite nucleation was also reported to effectively aggravate the ferrite orientation relationship with the mother austenite. 34) Figure 7 shows the results of the application of a small load (3 kNϭ26.5 MPa) during the ferrite transformation in a 0.15C-1.4Mn-0.3Si-0.02Ti-0.006B-0.03Al steel.…”
Section: Effect Of Applied Stress On the Ferrite Grain Formationmentioning
confidence: 99%
“…Hence particularly post-deformation is assumed to play an important roll in distributing the orientation of intergranular ferrite in 'dynamic' austenite-to-ferrite transformation. Lee and co-workers [25][26][27] have found that external stress during austenite-to-ferrite transformation has also the potential to distribute the orientation of intergranular ferrite. The combined effect of pre-/post-deformations and external stress on the orientation of intergranular ferrite may be a subject of the intense examination on dynamic transformation in a future.…”
Section: Role Of Pre-/post-deformations On the Orientationmentioning
confidence: 99%